Organisational Leadership: How Much Does It Matter? - Getinet Astatike Haile (Institute of Labor Economics (IZA), 2022)
We study the influence of leadership on organisational performance and worker wellbeing using data from the 2004 and 2011 Workplace Employment Relations Survey (WERS). Our most conservative estimates from fixed effects regressions on a panel of organisations reveal that virtuous leadership is significantly and positively linked to an upbeat assessment of organisational performance, and an increase in worker wellbeing. Specifically, the estimates reveal that an increase in leadership quality by one standard deviation increases organisational performance and worker job satisfaction by 0.27 and 0.73 standard deviations, respectively, while it leads to a fall in worker job anxiety by 0.13 standard deviations. The results support the hypothesis that good leadership is vital for the success of business including worker wellbeing, which organisational policy makers ought to heed. There is a dearth of evidence on organisational leadership as an institution and its influence on organisational outcomes, which this paper aims to address.
Keywords: I31; J28; J5; L2; M5; 330; leadership; organisational performance; worker wellbeing; linked data; Britain